SANS and SAXS investigation of the melt state structure in disentangled ultrahigh molecular weight polyethylene - Sharma, Aakash; Kruteva, Margarita; Willner, Lutz; Romano, Dario; Porcar, Lionel; Dulle, Martin; Zhou, Fuhai; Rastogi, Sanjay; Richter, Dieter (ACS Macro Letters, 2025)
Disentangled ultrahigh molecular weight polyethylene exhibits a time-dependent increase in rheology modulus when molten. This originates from its kinetically evolving heterogeneous microstructure consisting of disentangled and entangled regions. We report a quantitative analysis of this microstructure using X-rays and neutrons that capture the signatures of these regions. We analyze the absolute intensities to obtain the volume fraction and size distribution of the disentangled domains in the melt. Employing neutrons, we follow the changes in these parameters with time. The trends are qualitatively similar to those of the previous rheological observations. Our methodology also provides an experimental verification of the theoretical report by McLeish, T. C. B. Soft Matter 2007, 3 (1), 83-87, which predicts the presence of high density disentangled domains in a low density entangled matrix. The analysis presented here is a useful instrument for unveiling the origin of differences in the properties of polymers obtained through different processing routes.